Charge-based capacitance measurement free from charge injection induced errors - Ganesan Vishal (2018)
The measurement of capacitance by Charge Based Capacitor Measurement (CBCM) is the most widely used method currently. The reason behind is that the errors induced by the charge injection is effectively minimized. However, after analysing different Charge-Based Capacitance Measurement Techniques, the results so far show that the accuracy of the absolute value of the capacitance can still be improved. The improved Charge-Based Capacitance Measurement technique involves three transistor pairs where in one of the transistor pairs, the Pmos is replaced with Nmos. The method effectively reduces the charge injection flowing to the capacitor when the transistor is off and the capacitance value obtained is error-free. The measurement is carried out on the Traditional Charge-based Capacitance Measurement Circuit and the results are compared with the measurement performed using the improved technique and the accuracy of the absolute values of capacitance were discussed.